2015
DOI: 10.1002/jez.1907
|View full text |Cite
|
Sign up to set email alerts
|

A morphological novelty for feeding and sound production in the yellowtail clownfish

Abstract: The yellowtail clownfish Amphiprion clarkii is able to close its mouth very quickly by means of the cerato-mandibular (c-md) ligament, a synapomorphic trait of Pomacentridae joining the hyoid bar to the medial part of the lower jaw. This fast closure induces tooth collision, thus producing sounds that the clownfish uses during agonistic behaviors. To investigate whether this rapid jaw movement is also used during feeding, we analyzed the kinematics of sound production and feeding. Sound production, feeding on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
(33 reference statements)
1
19
0
Order By: Relevance
“…For all six species, we studied biting on food items fixed to tweezers (pieces of shrimp or mussel of roughly 1 cm long and 0.5 cm wide). The data for A. clarkii and S. rectifraenum come from our previous works (Olivier et al, 2015.…”
Section: High-speed Video Recordingsmentioning
confidence: 99%
See 4 more Smart Citations
“…For all six species, we studied biting on food items fixed to tweezers (pieces of shrimp or mussel of roughly 1 cm long and 0.5 cm wide). The data for A. clarkii and S. rectifraenum come from our previous works (Olivier et al, 2015.…”
Section: High-speed Video Recordingsmentioning
confidence: 99%
“…2c). High-speed video analyses revealed that the movements of the neurocranium and the hyoid apparatus are fast, which quickly tightens the ligament, ultimately allowing the fish to slam their mouth shut within 2-4 ms (Olivier et al, 2015Parmentier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations